(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Tuberculosis (Mycobacterium tuberculosis) in the world the most many widespread contagious from diseases one In this article, M. tuberculosis bacteria microbiological characteristics, processes of pathogenesis, man immune interact with the system effect and modern diagnosis methods about information given. Also, the microbiology of tuberculosis to medicines endurance mechanism and related to new therapeutic approaches aspects also seeing is out.